Pengetahuan Perawat tentang Sasaran Keselamatan Pasien dengan Kepatuhan Melakukan Identifikasi Pasien dengan Benar - Saptomo, Reska Budi; Hamzah, Amir; Ramadhani, Anggun Fajar; Alamsyah, Azhar Zulkarnain (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the relationship between nurses' knowledge of patient safety goals and correct patient identification. The method used is a quantitative study with a cross-sectional approach, sampling was carried out using purposive sampling of 92 respondents, data were collected through questionnaires and analyzed using the Chi-Square test. The results of this study showed a p-value of 0.000 (p < 0.05), which means there is a significant relationship between the level of knowledge and nurse compliance. Nurses with good knowledge tend to be highly compliant (83.6%), while those with sufficient knowledge are more likely to be non-compliant (8.8%). In conclusion, there is a relationship between nurses' knowledge of patient safety goals and compliance in correct patient identification. Keywords: Patient Identification Compliance, Nurse Knowledge, Patient Safety Goals